PE-Net: a parallel framework for 3D inferior mesenteric artery segmentation - Zhang, Kun; Xu, Peixia; Wang, Meirong; Lin, Pengcheng; Crookes, Danny; He, Bosheng; Hua, Liang (Frontiers in Physiology, 2023)
The structural morphology of mesenteric artery vessels is of significant importance for the diagnosis and treatment of colorectal cancer. However, developing automated vessel segmentation methods for this purpose remains challenging. Existing convolution-based segmentation methods have limitations in capturing long-range dependencies, while transformerbased models require large datasets, making them less suitable for tasks with limited training samples. Moreover, over-segmentation, mis-segmentation, and vessel discontinuity are common challenges in vessel segmentation tasks. To address these issues, we propose a parallel encoding architecture that combines transformers and convolutions to retain the advantages of both approaches. The model effectively learns position deviations and enhances robustness for smallscale datasets. Additionally, we introduce a vessel edge capture module to improve vessel continuity and topology. Extensive experimental results demonstrate the improved performance of our model , with Dice Similarity Coefficient and Average Hausdorff Distance scores of 81.64% and 7.7428 respectively.